Optimization BUMDes through Processing Of Banana Agricultural Products Into Banana Sale, To Obtain Added Value in Cihanjuang Village, Cibaliung - Deris Desmawan; Rizal Syaifudin; Sugeng Setyadi (MOVE: Journal of Community Service and Engagement, 2022)
One of the economic development efforts in Chihanjuang village is to develop a Badan Usaha Milik Desa (BUMDes). The purpose of this activity is to help improve the economy of the people of Chihanjuang village by providing people with understanding and skills in processing bananas into sale. Bananas are a considerable agricultural product in the village of Cihanjuang. The production of bananas is quite abundant at a low price, making BUMDes attempt to produce more high-value products. A lumpy banana sale is a finger sale process wrapped in a lumpy skin. Banana sale is a semi-wet food made from ripe bananas by drying, and frying. This community service activity was carried out on 15 August 2022 in Chihanjuang village by overseeing the development of village-owned enterprises (BUMDes) in agriculture, and practicing how to process lumpia banana sales to PKK cadres into a program that can boost the economy in the community.